Hyalinizing Granuloma: An Unusual Case of a Pulmonary Mass - Viviane Brandão; Edson Marchiori; Gláucia Zanetti; Guilherme Abdalla; Nina Ventura; Carolina Lamas Constantino; Mariana Leite Pereira; Pedro Martins; Rodrigo Canellas; Antonio Muccillo; Romulo Varella de Oliveira (Case Reports in Medicine)
We describe the case of pulmonary hyalinizing granuloma in a 34-year-old asymptomatic man who presented with a pulmonary nodule apparent by chest radiography and computed tomography (CT). He had a history of previous treatment for tuberculosis. His laboratory data were normal. Bronchoscopy and CT-guided percutaneous transthoracic fine needle aspiration cytology were inconclusive. The diagnosis was revealed after the histopathological examination of an open lung biopsy.